Explore the Economic Significance of the Dhakki Date Industry in the Local Region, Including its Contribution to Employment, Income Generation, and Overall Economic Development - Imran Qazi; Qazi Shoaib Ali; Muhammad Saad; Zeeshan Ahmad; Muhammad Usman Khanb; Muhammad Kamran Rabbi; Mujeeb ur Rahman (Indus Journal of Bioscience Research, 2023)
Background: The cultivation of Dhakki dates has enormous economic significance in the surrounding area, contributing significantly to employment, income generation, and overall economic development. Objectives: This study investigated the economic significance of the Dhakki date industry in the local region, with a focus on its contribution to employment, income generation, and overall economic development. Methods: Through a comprehensive research approach, utilizing both primary and secondary data sources, significant numerical values were obtained. Results: The findings revealed that date farming had created 2520 jobs for date farmers, 30240 jobs for laborers, 35 jobs for merchants and wholesalers, and 78 jobs for exporters. In terms of income generation, small-scale farmers earned an average annual income ranging from 25,00,000 to 35,00,000 PKR, while large-scale farmers generated an average annual income ranging from 70,00,000 to 80,00,000 PKR. These figures highlighted the substantial contributions of the Dhakki date industry to employment and income generation in the past. Moreover, the study emphasized the importance of cultivation practices and processing techniques in maximizing productivity and enhancing marketability. Conclusion: The findings of this research provided valuable insights for policymakers and stakeholders, facilitating informed decision-making and supporting the past growth and development of the Dhakki date industry.